Friction material

JP2026165835APending Publication Date: 2026-10-14AKEBONO BRAKE IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058440
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165835000001
    Figure 2026165835000001
  • Figure 2026165835000002
    Figure 2026165835000002
Patent Text Reader

Abstract

To provide a friction material that maintains a high coefficient of friction before and after thermal history and exhibits low wear on the mating material. [Solution] A friction material comprising a fiber base material, a friction modifier, and a binder, wherein the friction modifier contains an inorganic abrasive with a Mohs hardness of 5 or more, graphite, and petroleum coke, the content of the inorganic abrasive in the friction material is 20% by mass or more, and the total content of the graphite and petroleum coke in the friction material is more than 4% by mass and less than 10% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a friction material used in automobiles, railway vehicles, industrial machinery and the like.

Background Art

[0002] The friction material is used in brakes such as disc brakes and drum brakes, clutches and the like, and plays a braking role by friction with a counterpart material such as a disc rotor. Performance required for the friction material includes maintaining a high friction coefficient, low counterpart material aggressiveness, and the like. Maintaining a high friction coefficient includes effectiveness characteristics in an initial state before being subjected to thermal history due to high load (initial effectiveness characteristics) and characteristics in which the friction coefficient is less likely to decrease after thermal history due to high load (fade resistance). The counterpart material aggressiveness refers to a characteristic of excessively abrading the counterpart material such as a disc rotor during traveling.

[0003] As a friction material excellent in fade resistance, for example, Patent Document 1 discloses a friction material containing a metal sulfide.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] However, in recent years, from the viewpoint of environmental consideration, it is expected that a friction material containing no metal sulfide will be demanded.

[0006] In view of the above circumstances, the present invention aims to provide a friction material that maintains a high friction coefficient before and after thermal history and has low counterpart material aggressiveness.

Means for Solving the Problems

[0007] As a result of diligent research, the inventors of the present invention have found that the above problems can be solved by including an inorganic abrasive of a specific hardness, graphite, and petroleum coke as a friction modifier, and by setting the content of each within a specific range, thereby completing the present invention. In other words, the present invention is as follows: <1> ~ <9> This concerns... <1> A friction material comprising a fiber base material, a friction modifier and a binder, The friction modifier contains an inorganic abrasive with a Mohs hardness of 5 or higher, graphite, and petroleum coke. The inorganic abrasive content in the friction material is 20% by mass or more. A friction material wherein the total content of graphite and petroleum coke in the friction material is greater than 4% by mass and less than 10% by mass. <2> The petroleum coke content is greater than 2% by mass and less than 6% by mass. <1> The friction material described above. <3> The average particle size of the aforementioned graphite is less than 200 μm. <1> or <2> The friction material described above. <4> The inorganic abrasive content is 20.5 to 23.0% by mass. <1> ~ <3> The friction material listed in any one of the following. <5> The inorganic abrasive material includes one or more selected from the group consisting of zirconium oxide, zirconium silicate, iron(III) oxide, and magnesium oxide. <1> ~ <4> The friction material listed in any one of the following. <6> The petroleum coke content exceeds the graphite content. <1> ~ <5> The friction material listed in any one of the following. <7> The mass ratio of the graphite content to the petroleum coke content is 1:1.1 to 1:2. <1> ~ <6> The friction material listed in any one of the following. <8> The metal sulfide content is 0.5% by mass or less. <1> ~ <7> The friction material listed in any one of the following. <9> The copper content is 0.5% by mass or less in terms of copper element. <1> ~ <8> The friction material listed in any one of the following. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide a friction material that maintains a high coefficient of friction before and after the thermal history and has low aggressiveness towards the mating material. [Modes for carrying out the invention]

[0009] The present invention will be described in detail below, but these are merely examples of embodiments and the present invention is not limited to these.

[0010] In this specification, the average particle diameter can be determined by the value of the volume-based cumulative percentage equivalent particle diameter (D50) measured by a laser diffraction particle size distribution analyzer.

[0011] The friction material according to an embodiment of the present invention (hereinafter also referred to as "the friction material of this embodiment") includes a friction modifier, a binder, and a fibrous base material. The following provides a detailed explanation of each component.

[0012] <Friction adjustment material> Friction modifiers are used to impart desired friction properties, such as wear resistance, heat resistance, and fade resistance, to friction materials.

[0013] In the friction material of this embodiment, the friction modifier contains an inorganic abrasive with a Mohs hardness of 5 or higher. This allows for a high coefficient of friction before thermal history, thereby enhancing the initial effectiveness, and also allows for a high coefficient of friction after thermal history, thereby improving fade resistance. The Mohs hardness of the inorganic abrasive is preferably 5.5 or higher, and preferably 9 or lower. Examples of inorganic abrasives with a Mohs hardness of 5 or higher include zirconium oxide, aluminum oxide, silica, magnesium oxide, zirconium silicate, chromium oxide, iron(II,III) oxide (Fe3O4), and chromite. These can be used individually or in combination of two or more. In particular, from the viewpoint of maintaining a high coefficient of friction while keeping the aggressiveness towards the mating material low, it is more preferable to include one or more selected from the group consisting of zirconium oxide, zirconium silicate, iron(II,III) oxide, and magnesium oxide.

[0014] In the friction material of the present embodiment, the content of the inorganic abrasive having a Mohs hardness of 5 or more is 20 mass% or more. By containing the inorganic abrasive in such a range, a high friction coefficient can be maintained before and after thermal history. The content of the inorganic abrasive having a Mohs hardness of 5 or more is preferably 20.5 to 23.0 mass%.

[0015] In the friction material of the present embodiment, the friction modifier contains graphite and petroleum coke. Graphite and petroleum coke function as lubricants. When the friction material contains these components, sufficient lubricity is exhibited even when a large amount of the inorganic abrasive having a Mohs hardness of 5 or more is contained as described above, so that the aggressiveness to the mating material can be suppressed to a low level.

[0016] In the friction material of the present embodiment, the total content of graphite and petroleum coke is more than 4 mass% and less than 10 mass%. When the total content of graphite and petroleum coke exceeds 4 mass%, sufficient lubricity is exhibited, so that the aggressiveness to the mating material can be suppressed to a low level, and when the total content is less than 10 mass%, the friction coefficient before thermal history can be maintained at a high level, and the effectiveness in the initial state can be enhanced. The total content of graphite and petroleum coke is preferably 5 to 7 mass%. Further, from the viewpoint of maintaining a higher friction coefficient before thermal history while suppressing the aggressiveness to the mating material to a low level, the content of petroleum coke preferably exceeds the content of graphite, and the mass ratio of the content of graphite to petroleum coke is more preferably 1:1.1 to 1:2.

[0017] The content of petroleum coke in the friction material of the present embodiment is preferably more than 2 mass% and less than 6 mass% from the viewpoint of securing the friction coefficient before thermal history. The content of graphite in the friction material of the present embodiment is preferably more than 1 mass% and less than 4 mass% from the viewpoint of securing the friction coefficient before thermal history while suppressing the aggressiveness to the mating material to a low level.

[0018] As the graphite, it is preferable to use graphite having an average particle size of less than 200 μm. Graphite with an average particle size of less than 200 μm has high lubricity, so even when the total content of graphite and petroleum coke is within the above range, a friction material with low aggressiveness to mating materials can be more easily obtained. Examples of the graphite include natural graphite and artificial graphite, which may be used alone or in combination of two or more. As the natural graphite, it is preferable to use flake graphite.

[0019] As the petroleum coke, it is preferable to use petroleum coke having an average particle size of 10 to 150 μm from the viewpoint of securing a friction coefficient.

[0020] However, from the viewpoint of reducing environmental load, the friction material of this embodiment preferably has a metal sulfide content of 0.5 mass% or less. A small amount of metal sulfide may be unavoidably contained in the friction material, but it is preferred that the metal sulfide is not substantially contained from the viewpoint of reducing environmental load. Examples of the metal sulfide include antimony trisulfide, molybdenum disulfide, and tin sulfide.

[0021] Examples of friction modifiers other than those described above include organic fillers, inorganic fillers, and metal powders.

[0022] Examples of the organic filler include various rubber powders (raw rubber powder and the like), rubber dust (tire tread and the like), resin dust, cashew dust, and melamine dust. These may be used each alone or in combination of two or more.

[0023] The content of the organic filler in the friction material of this embodiment is preferably 1 to 15 mass%, more preferably 1 to 10 mass%.

[0024] Examples of inorganic fillers include titanates such as potassium titanate, lithium titanate, lithium potassium titanate, sodium titanate, calcium titanate, magnesium titanate, and magnesium potassium titanate, as well as inorganic materials such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica. These can be used individually or in combination of two or more.

[0025] The inorganic filler content in the friction material of this embodiment is preferably 30 to 80% by mass, more preferably 40 to 70% by mass.

[0026] Examples of metal powders include aluminum, tin, and zinc powders. These can be used individually or in combination of two or more types.

[0027] The metal powder content in the friction material of this embodiment is preferably 1 to 10% by mass, more preferably 1 to 5% by mass.

[0028] From the viewpoint of sufficiently imparting the desired friction characteristics to the friction material, the friction modifier is preferably used in an amount of 60 to 90% by mass, more preferably 70 to 90% by mass, of the entire friction material.

[0029] <Binding material> The binder is used to integrate the fibrous base material and friction modifier contained in the friction material. Various commonly used binders can be used as the binder. Specifically, examples include phenolic resins, various modified phenolic resins such as elastomers, thermosetting resins such as melamine resins, epoxy resins, and polyimide resins.

[0030] Examples of elastomer-modified phenolic resins include acrylic rubber-modified phenolic resins, silicone rubber-modified phenolic resins, and nitrile rubber (NBR)-modified phenolic resins. These can be used individually or in combination of two or more types.

[0031] From the viewpoint of the formability of the friction material, the binder is preferably used in an amount of 1 to 20% by mass, more preferably 3 to 15% by mass, of the entire friction material.

[0032] <Textile base material> Fiber base materials are used to add strength to friction materials. Examples of fiber base materials include organic fibers, inorganic fibers, and metal fibers. These fiber base materials can be used individually or in combination of two or more types.

[0033] Examples of organic fibers include aromatic polyamide (aramid) fibers and flame-resistant acrylic fibers.

[0034] Examples of inorganic fibers include biosoluble inorganic fibers, ceramic fibers, alumina fibers, glass fibers, carbon fibers, and rock wool. Examples of biosoluble inorganic fibers include biosoluble ceramic fibers such as SiO2-CaO-MgO fibers, SiO2-CaO-MgO-Al2O3 fibers, and SiO2-MgO-SrO fibers, as well as biosoluble rock wool.

[0035] Examples of metal fibers include steel fibers, etc.

[0036] From the viewpoint of ensuring the strength of the friction material, the fibrous base material is preferably used in an amount of 3 to 30% by mass, and more preferably 5 to 20% by mass, of the entire friction material.

[0037] The friction material of this embodiment preferably has a copper content of 0.5% by mass or less in terms of copper element. Although a small amount of copper may inevitably be present in the friction material, it is preferable that it be substantially free of copper from the viewpoint of reducing environmental impact.

[0038] <Manufacturing method for friction materials> The friction material of the present invention can be manufactured by known manufacturing processes. For example, the above components can be blended, and the blended material can be manufactured by pre-molding, thermoforming, heating, polishing, and other processes according to a conventional manufacturing method.

[0039] The manufacturing method for brake pads equipped with friction material generally involves the following steps. (a) A process of forming a pressure plate into a predetermined shape using a sheet metal press. (b) The process of degreasing, chemical treatment and primer treatment on the above pressure plate and applying adhesive. (c) A process of blending raw materials such as friction modifiers, binders and fiber base materials, thoroughly homogenizing them by mixing, and molding them at room temperature under a predetermined pressure to produce a pre-molded body. (d) A thermoforming process in which the above-mentioned pre-molded body and the pressure plate to which adhesive has been applied are fixed together as a single unit by applying a predetermined temperature and pressure (molding temperature 130-180°C, molding pressure 30-80 MPa, molding time 2-10 minutes). (e) After-curing (150-300°C, 1-5 hours), the final finishing process involves polishing, scorching, and painting. [Examples]

[0040] The present invention will be described in more detail below using examples, but the present invention is not limited to these.

[0041] (Examples 1-4, Comparative Examples 1-5) The ingredients shown in Table 1 were all added to a mixing and stirring machine and mixed at room temperature for 4 minutes to obtain the mixture. The resulting mixture was subjected to the following steps to produce a friction material: (i) pre-forming, (ii) thermoforming, (iii) heat treatment, and scorching.

[0042] (i) Preformation The mixture was placed into the mold of a pre-forming press, and a pre-molded body was produced by molding at room temperature under 20 MPa for 10 seconds. (ii) Thermoforming This pre-molded body was placed in a thermoforming mold, a metal plate (pressure plate) with adhesive applied beforehand was placed on top, and the mold was heated and pressurized at 150°C and 40 MPa for 5 minutes. (iii) Heat treatment, scorching This heated and pressurized molded body was subjected to a heat treatment at 250°C for 3 hours, after which the surface was polished. Next, the surface of this heated and pressurized molded body was subjected to a scorching treatment, and then painted as a finish to obtain a friction material.

[0043] The friction materials obtained in Examples 1-4 and Comparative Examples 1-5 were evaluated for their initial effectiveness, effectiveness after thermal history, and mating material aggressiveness using the following methods.

[0044] <Initial efficacy characteristics (efficacy characteristics before thermal history)> Using the friction material and disc rotor obtained above, tests were conducted under the conditions shown in Table 1 to evaluate the initial effectiveness characteristics. Normal braking performance: At an initial speed of 70 km / h and a brake fluid pressure of 4 MPa, the coefficient of friction during braking was measured, and the average value of the coefficient of friction was evaluated based on the following criteria. An A rating was considered good. A: Average coefficient of friction is 0.39 or higher C: Average coefficient of friction is less than 0.39

[0045] <Fade resistance (effectiveness characteristics after thermal history)> Using the friction material and disc rotor obtained above, tests were conducted under the conditions shown in Table 1 to evaluate the effectiveness characteristics after thermal history. Effectiveness Check: At an initial speed of 70 km / h, the coefficient of friction was measured at each deceleration point shown in Table 1, and the average value of the coefficient of friction was evaluated based on the following criteria. A value of A was considered good. A: Average coefficient of friction is 0.34 or higher C: Average coefficient of friction is less than 0.34

[0046] Effectiveness at different speeds: The coefficient of friction was measured at initial speeds of 65 km / h and 135 km / h, and the difference in effectiveness was calculated using the following formula. Effectiveness difference = (Friction coefficient at 135 km / h - Friction coefficient at 65 km / h) / Friction coefficient at 65 km / h × 100 The difference in effectiveness was evaluated based on the following criteria. An A rating was considered good. A: The difference in effectiveness is less than 13.5% C: Difference in effectiveness is 13.5% or less

[0047] <Aggression towards opponents> Using the friction material and disc rotor obtained above, tests were conducted under the conditions shown in Table 1, and the amount of disc rotor wear was measured from the difference in thickness of the disc rotor before and after the test. The measured disc rotor wear was evaluated based on the following criteria. A score of A or B was considered good. A: Wear amount is less than 12 μm B: Wear amount is 12 μm or more but less than 15 μm C: Wear amount is 15 μm or more

[0048] The results of each of the above evaluations are shown in Table 2.

[0049] [Table 1]

[0050] [Table 2]

[0051] The results in Table 2 show that the friction materials of Examples 1 to 4 maintained high coefficients of friction in both their initial effectiveness and effectiveness after thermal history, and also exhibited low aggressiveness towards the mating material. On the other hand, the friction material of Comparative Example 1, which had a total content of petroleum coke and graphite exceeding 10% by mass, showed a decrease in the coefficient of friction after the thermal treatment. The friction material of Comparative Example 2, which had a total content of petroleum coke and graphite of 4% by mass or less, showed high aggressiveness towards the mating material. The friction material of Comparative Example 3, which had an abrasive content of less than 20% by mass, showed a decrease in friction performance both initially and after the thermal treatment. The friction material of Comparative Example 4, which did not contain petroleum coke, and the friction material of Comparative Example 5, which did not contain graphite, showed differences in the effectiveness of the coefficient of friction after the thermal treatment, and also showed high aggressiveness towards the mating material.

Claims

1. A friction material comprising a fiber base material, a friction modifier and a binder, The friction modifier contains an inorganic abrasive with a Mohs hardness of 5 or higher, graphite, and petroleum coke. The inorganic abrasive content in the friction material is 20% by mass or more. A friction material wherein the total content of graphite and petroleum coke in the friction material is more than 4% by mass and less than 10% by mass.

2. The friction material according to claim 1, wherein the petroleum coke content is more than 2% by mass and less than 6% by mass.

3. The friction material according to claim 1 or claim 2, wherein the average particle size of the graphite is less than 200 μm.

4. The friction material according to claim 1 or claim 2, wherein the content of the inorganic abrasive is 20.5 to 23.0% by mass.

5. The friction material according to claim 1 or claim 2, wherein the inorganic abrasive material comprises one or more selected from the group consisting of zirconium oxide, zirconium silicate, iron(III) oxide, and magnesium oxide.

6. The friction material according to claim 1 or claim 2, wherein the content of petroleum coke exceeds the content of graphite.

7. The friction material according to claim 1 or claim 2, wherein the mass ratio of the graphite content to the petroleum coke content is 1:1.1 to 1:

2.

8. The friction material according to claim 1 or claim 2, wherein the content of metal sulfides is 0.5% by mass or less.

9. The friction material according to claim 1 or claim 2, wherein the copper content is 0.5% by mass or less in terms of copper element.

Citation Information

Patent Citations

  • Friction material

    JP2017095646A